Feasibility, acceptability, and appropriability of a national whole-school program for reducing school violence and improving school coexistence - Rojas-Andrade, Rodrigo; Lopez Leiva, Verónica; Varela, Jorge J.; Soto García, Pamela; Álvarez, Juan Pablo; Ramirez, María Teresa (Frontiers in Psychology, 2024)
The increase in school violence after the COVID-19 pandemic calls for schools to adopt a whole-school, multilevel approach. This study assessed the feasibility of a national program designed by the Chilean Ministry of Education in collaboration with universities. Designed as part of the Ministry´s Educational Reactivation Plan, it improves school climate management in Chilean schools following a multi-level whole-school approach. The program design and initial implementation in all 16 regions of Chile included school climate networks, direct intensive university technical assistance, and professional development and training. The feasibility, acceptability, and appropriability of the "Learning to Live Together Program" (LLT) was assessed through a survey applied to N= 1,561 members of the staff of 783 schools in all regions of Chile. Participants responded to a battery of instruments that measured acceptability, appropriability, feasibility, attitudes toward implementation, fidelity, and perceived initial results. The results showed high initial adoption and significant improvements in the assessed dimensions. The improvement of school climate practices and strengthening of the school collaboration network were highly relevant. These findings provide evidence that the WSA approach may be an effective strategy for Latin American countries and provides essential data for educational and government decisions. The study also indicates that the results may be applicable to the implementation of similar policies in other contexts or countries.